PENGARUH PENGEMBANGAN KARIR, PENEMPATAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DAN DAMPAKNYA PADA KINERJA DINAS PENDIDIKAN ACEH - Muchlis Muchlis; Amri Amri; M. Sabri Abdul Majid (Departemen Manajemen, Universitas Syiah Kuala, 2017)
ABSTRACT This study aimed to analyze the influence of career development, placement, motivation and work environment towards employee performance either simultaneously or partially and its impact on Education Department of Aceh. The research population is all employees of the Education Department of Aceh the number of 440 people. The total sample of 115 people with a sampling technique using Slovin formula. Data analysis method used is path analysis. The results showed that 1) Career development, placement, motivation and working environment have a significant effect both simultaneously and partially on the employee performance, 2) career development, placement, motivation and work environment on the Education Department of Aceh performance, 3) Employee Performance significantly affect the Education Department of Aceh performance, 4) the employee performance capable of acting as a partial mediator between the influence of career development, placement, motivation and work environment to Education Department of Aceh performance. The implications of this research, the need for policy review financial management, maximize existing resources, open job posting, giving rewards to employees and repair equipment. Keywords: Career Development, Placement, Motivation, Work Environment, Employee Performance and Organizational Performance